2017 Excavation report of rabat cemetery in Boysun, Uzbekistan - Bin, Liu; Yun, Liang (Acta Archaeologica Lodziensia, 2025)
In 2017, the Joint Central Asia Archaeological Team of China and Uzbekistan conducted excavation in the Cemetery No.1 on the north of Rabat Village. The excavation recovered 52 burials, of which 37 were earthen cave burials with sideway chamber, 11 were vertical earthen shaft pit burials, and four had unidentifiable forms. The burial occupants were mostly in extended supine position heading north, and the grave goods unearthed from these burials included pottery wares, bronzes, iron objects, stone implements, glass wares, etc. The burial structures and artifacts unearthed from these burials all had unique characteristics compared to their counterparts found in the nearby areas, and the date of this cemetery is from the end of the 2nd century BC to the early 1st century AD. It would be the remains of the Da Yuezhi (Greater Yuezhi) people and could be named as Yuezhi Culture. The excavation of this cemetery provided important data for the archaeological exploration of the Greater Yuezhi people.